Cost-benefit analysis of a one-server two-unit system subject to shock and degradation - Gopalan, M.N.; Ramesh, T.K. (Microelectronics and reliability, 1986)
This paper deals with the cost-benefit analysis of 1-server 2-unit system subject to two modes of failure, namely, shock and degradation. Initially, one unit starts operating and the other is kept as cold-standby. The type of repair a unit undergoes depends upon the nature of its failure. The various essential characteristics of the system have been found out to carry out the cost-benefit analysis.